Determination of the fine structure of a halide perovskite using THz spectroscopy - Zhang, Feng (2020)
In a crystalline solid, many types of disorders exist. Revealing the localized structures induced by disorder is one of the central issues of crystallography. Retrieving information about disorder from the scattering patterns of X-ray and/or neutron diffractions is still facing vital challenges. New experimental observations, whenever available, are greeted to shed additional light on this problem. We have in one previous work demonstrated a ubiquitous capability of terahertz (THz) spectroscopy to detect the fingerprint vibrational peaks of correlated molecular arrangements at the nano-scale level in an occupation disorder system.[1] We will, in this work, employ THz spectroscopy to study the fine structure of the halide perovskite systems where the short-range order of the disordered methylammonium (MA) molecules remains an open question.